La excesiva onerosidad de la prestación en contexto del COVID-19: ¿perdona nuestras deudas así como nosotros perdonamos a nuestros deudores? - Espinoza Espinoza, Juan (2024)
The purpose of this article is to offer a review on the excessive onerousness of the performance and the way in which this figure was affected by the appearance of the COVID-19 pandemic in 2020.The author analyzes the different articles of the Peruvian Civil Code related to the subject and applies them to the Emergency and Supreme Decrees emitted in quarantine in order to elucidate if we were in an irresistible, extraordinary and unforeseeable situation to be able to invoke the excessive onerousness of the performance.